2017
DOI: 10.1177/1933719116678688
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanins and Mouse Oocyte Microvilli Related to Fertilizing Ability

Abstract: Our electron microscopy observations demonstrate for the first time that the number of microvilli on the mice oocyte membrane decreases when meiosis progresses from prophase I to metaphase II (MII) stage, and the morphology of the microvilli also changes. Microvilli are significantly shorter and larger on the ovulated oocyte membrane than at the previous stages. Although clathrin vesicles clearly disappear during oocyte maturation, exosome-like vesicles begin to be secreted at the metaphase I stage, more stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…To validate these protocols, we imaged zona-free eggs from Cd9 Null female mice. CD9 is a tetraspanin protein that localizes to microvilli of membranes 53 and Cd9 Null eggs have an altered membrane due to varied length, thickness and density of their microvilli 54 . Projected confocal images detected a >1.5-fold reduction in the fluorescent intensity of Cd9 Null compared to wild-type eggs (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To validate these protocols, we imaged zona-free eggs from Cd9 Null female mice. CD9 is a tetraspanin protein that localizes to microvilli of membranes 53 and Cd9 Null eggs have an altered membrane due to varied length, thickness and density of their microvilli 54 . Projected confocal images detected a >1.5-fold reduction in the fluorescent intensity of Cd9 Null compared to wild-type eggs (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in our study, Plac1 enriched on the cell membrane, presumably via its ZP-like domain, and Plac1 knockdown caused the abnormal distribution of cortical microvillus. As an irregular microvillar shape and organization contribute to the abnormal fertilization of mouse oocytes (20)(21)(22), this could account, in part, for the decreased fertilization after Plac1 knockdown. In contrast, Plac1 knockdown significantly decreased Akt phosphorylation, as Akt is well known to play an important role in the mitotic cell cycle and in meiosis (23,24), and we also showed that Akt inhibition significantly perturbed meiosis progression (reduced MII rate).…”
Section: Discussionmentioning
confidence: 99%
“…Gene knock-out studies demonstrated that these molecules are either non-essential or compensable in mouse fertilization (Primakoff and Myles, 2007). Alternatively proposed sperm receptors on the oollema, tetraspanins CD9 and CD81 were knocked out, resulting in reduced fertility of single gene knock-out and complete infertility of double knock-out (Benammar et al 2016). The most convincing evidence for gamete adhesion receptors came with the discovery of the sperm-specific immunoglobulin family cell adhesion protein IZUMO (Inoue et al, 2005) and its oocyte-binding partner, the folate-binding receptor JUNO (Bianchi et al, 2014).…”
Section: Gamete Adhesion and Fusion And Sperm Incorporationmentioning
confidence: 99%